The Competencies of the Supply Chain Management in the System of Economic Security of Russian Enterprises - Tatyana Anatolyevna Snetkova; Pavel Alexandrovich Aletkin; Svetlana Sergeevna Meleshenko (International Journal of Supply Chain Management, 2020)
Abstract— The level of economic security of an entity is heavily influenced by administrative and legal status of Supply chain management. Legal status of Supply chain management determined specifics of his work. Supply chain management belongs to the leaders of the economic-financial and administrative units of the organization. Emphasis on professional competence, labour functions and legal status of Supply chain management in ensuring the economic security of an entity in the light of the introduction in Russian practice of a professional standard